Evidenciation of Environmental Management: An Evaluation with Item Response Theory’ - Trierweiller, Andréa Cristina; Peixe, Blênio César Severo; Tezza, Rafael; Bornia, Antonio Cezar; De Souza, Lucila Maria (Brazilian Journal of Operations & Production Management, 2013)
The aim of this article is to measure the evidence ofEnvironmental Management using the Item Response Theory, based on website analysis from Brazilian industrial companies. This is a qualitative, exploratory, and descriptive study related to an information collection and analysis instrument. Primary data was gathered from 638 company websites from 10 different Brazilian sectors: (1) Agricultural Production, (2) Automotive, (3) Chemicals and Petrochemical, (4) Construction, (5) Energy, (6) Paper, (7) Steel and Metals, (8) Information Technology, (9) Mining and (10) Textile. There was the creation of 26 items approved by environmental specialists. The results were attained with the measuring of Environmental Management evidence via the Item. Response Theory, providing a clear order of the items involved based on each item’s level of difficulty, quality, and propriety. This permitted the measurement of each item’s quality and propriety, as well as that of the respondents, placing them on the same analysis scale. Increasing the number of items involved is suggested for future research in order to permit broader sector analysis. It would also be interesting to build a Computerized Adaptive Test (CAT) for the respondent – the end of the questionnaire – get, immediately, the degree of environment management evidence of your company. As such, a greater reach of the instrument should be considered with the objective to contribute to business management.